Case report: Self-administration of alpha-1 antitrypsin therapy: a report of two cases - Escribano Dueñas, Ana M.; Martín García, Mónica; Tortajada Goitia, Begoña; Arenas Villafranca, José Javier (Frontiers in Pharmacology, 2023)
Intravenous augmentation therapy with human alpha-1 proteinase inhibitor for the management of respiratory disease is recommended for people with alpha-1 antitrypsin deficiency (AATD) who are nonsmokers or former smokers. Augmentation therapy usually requires weekly administration at the hospital or clinic and poses an additional burden for patients due to interference with daily life, including work and social activities. Self-administration is a useful alternative to overcome this limitation, but there is a lack of published information on clinical outcomes. We report two cases of individuals with AATD at different stages of the disease who were successfully managed with self-administered augmentation therapy, with increased satisfaction because of the independence gained, lack of interference with clinical stability, and no relevant safety issues.